Sustaining social balance and peace in the post-Covid-19 pandemic: a study in the light of maqasid al-sharia’h approach - Bendebka, Ramzi; Fettane, Amar; Shogar, Ibrahim Adam Ahmed (IIIT East and Southeast Asia, 2023)
The spread of COVID-19 disease since the end of 2019 has led to social functions and activities disorders in our societies. The pandemic has had a significant influence on social balance and peace. This situation has raised awareness that a more sustainable model is needed. The study assumes that the Maqasid al-Shariah approach can provide comprehensive social sustainability and protection solutions. Therefore, we offer analyses of the social dimensions during the disease and its impact on balance and peace, evaluate authorities' role in providing solutions to current issues and problems, and determine the possible answers based on the Maqasid al-Shariah approach. The study adopted the analytical approach, looked into policies and social dimensions, and discussed the different views of the policy-makers and scholars by explaining their authorities on the issue and then analysing the problems in the light of maqasid al-Shariah. The expected results are that the main reasons for rising social issues during the pandemic are the lack of clear plans for the post-COVID-19 and the general focus policies on technical matters, like lockdown policies and economic affairs focusing on people's needs protection. The expected outcomes also show that social issues are contrary to maqasid al-Shariah, which is based on protecting life, intellect, and wealth. Therefore, it is necessary to align policies and plans with maqasid teachings, stick to its maqasid, and implement them in social affairs. Social balance and peace will be sustained and protected in the post-COVID-19 era.